Protective effects of major royal jelly proteins on reproductive function of mice during perimenopausal period - LIU Xin; CHEN Yong; SHEN Lirong (浙江大学学报. 农业与生命科学版)
In order to study the effects of the major royal jelly proteins (MRJPs) on the endocrine endocrinology in female mice during the perimenopausal period, an experiment was conducted for the natural aging female ICR mice with the age of 11-13 months. Fifty female mice were randomly divided into five equal groups, including low, middle and high dose groups of MRJPs (administrated with 125, 250, 500 mg/kg MRJPs, respectively), positive control group (administrated with 125 mg/kg casein) and old model group (administrated with physiological saline). Meanwhile, ten female mice with the age of five months were set as the young control group (administrated with physiological saline). Intragastric administrations were conducted for seven weeks once daily continuously. The indexes of uterus and ovary were calculated, and serum levels of estradiol (E2), progesterone (P), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) were detected by radioimmunoassay. The real-time polymerase chain reaction was used to detect the expressions of estrogen receptor α (ERα), estrogen receptor β (ERβ) and progesterone receptor (PR). The histomorphological observation of the uterus and ovary was also carried out under an optical microscope. The results showed that MRJPs supplement in the medium and high dosages could increase the uterus index and ovary index. Serum levels of E2 and P were significantly elevated in the MRJPs groups, while the levels of FSH and LH were decreased as compared with the old model group. The expressions of ovarian ERα, ERβ and PR were up-regulated significantly in the MRJPs groups. Follicular development was also improved. In conclusion, the above results suggest that MRJPs possess the protective activity in reproduction of mice during the perimenopausal period. It provides scientific evidences of royal jelly and MRJPs in prevention and improvement of perimenopause syndrome.